Strengthening The Psychosocial Support of The Elderly Through Empathic Communication Training for Young Volunteers at The KG Elderly Home, Kediri Regency - Fitriya, Laelatul; Pratikto, Herlan; Sa’adati, Tatik Imadatus (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The elderly population in Indonesia has experienced a significant increase that has complex consequences for psychosocial well-being, especially for the displaced elderly who experience disconnection from family relationships and lack of emotional support. This study aims to analyze the effectiveness of empathic communication training for young volunteers in improving psychosocial support for the abandoned elderly at the KG Elderly House, Kediri Regency.  Data collection was carried out through naturalistic observation for one week, semi-structured interviews, and Focus Group Discussions involving the elderly, young volunteers, administrators, and active volunteers. The results of the study showed that the elderly experienced loneliness, prolonged sadness, social withdrawal, and difficulty achieving ego integrity which was aggravated by the limitations of psychosocial support. Empathetic communication training for 18 young volunteers was shown to improve the quality of emotional interaction, social engagement of the elderly, and feelings of being valued and cared for. The findings integrate Erikson's theory of psychosocial development,  Lazarus and Folkman's theory of stress and coping stress  , and Bronfenbrenner's theory of ecology in understanding problems holistically. This study recommends the development of sustainable psychosocial mentoring programs, strengthening the capacity of volunteers, and cross-sectoral collaboration to improve the welfare of the marginalized elderly.